Online health information system BD doctor - Hossain, Jahangir; Hasan, A. T. M. Mahmudul (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2006.